PROMOTING VOCABULARY ENRICHMENT THROUGH QUIZIZZ ENGAGEMENT IN INDONESIAN VOCATIONAL SCHOOL : A QUALITATIVE STUDY - Wulaningrum, Eva; Novitasari , Devi (English Language Teaching Methodology, 2024)
This study is an investigation of the use of Quizizz as a learning media to promote vocabulary. This research uses a qualitative case study approach by conducting observations, interviews, and reflective journals to collect in-depth information about the use of Quizizz in vocabulary enrichment. The subjects of this study were 11th-grade students in the couture major at one of the vocational schools, totalling 14 students. In the research, it was found that students felt motivated and engaged to use Quizizz because of the features that made its use more fun. It can be concluded that this study has progressed in terms of student vocabulary enrichment. Thus, Quizizz proved to be effective as an additional learning media because the interesting features in it make students motivated and active in class. This finding shows that integrating Quizizz into classroom teaching can have a positive impact on students' vocabulary learning.